30x+12=56x+49

Simple and best practice solution for 30x+12=56x+49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30x+12=56x+49 equation:



30x+12=56x+49
We move all terms to the left:
30x+12-(56x+49)=0
We get rid of parentheses
30x-56x-49+12=0
We add all the numbers together, and all the variables
-26x-37=0
We move all terms containing x to the left, all other terms to the right
-26x=37
x=37/-26
x=-1+11/26

See similar equations:

| 14x-131=5x-14 | | 8-p=-12-3p* | | 4k-24=-2k-12 | | a§5+8=16 | | 4x+13=-137-10x | | 7x-13=-x-5 | | F(x+8)=5x+6 | | 6(x-2)-(3-2x)=3(x-4) | | 2x+5-3x-4+5x=2+2x-4 | | 3a-9=2a-4 | | 5y+3-2y=11-y+16 | | 5y+3-2y=11-y+16* | | 8x+12-3+3x=3-2+x+2x | | 9.7+x=13.2 | | 9x2=3 | | 3x2=41 | | 6x-9=2x+16 | | 8x-12=35x+24 | | 3x2=22 | | 6x-16=-2,8 | | -6-7v=4v+65 | | 5x+12=11-10x | | 3,5x+18=25 | | 8y+4=3y-10 | | 6x2=11 | | 3(3s+7)=48 | | -3x+x=9 | | -2(5x+9)=2(-4x) | | 27x-6=14x-49 | | 175-11x=120 | | 75+x+135+x=360 | | 3x+6=14-2× |

Equations solver categories